Atypical Avian Influenza (H5N1) - Apisarnthanarak, Anucha (Centers for Disease Control and Prevention, 2004)
We report the first case of avian influenza in a patient with fever and diarrhea but no respiratory symptoms. Avian influenza should be included in the differential diagnosis for patients with predominantly gastrointestinal symptoms, particularly if they have a history of exposure to poultry.